NEUROLOGIC DEFICIT AND LEVEL OF CONSCIOUSNESS IN PATIENTS AFTER STROKE: CORRELATION WITH RISK FACTORS - Angelova, Aleksandra; Gashpar, Glorija; Arsovska, Anita (Journal of Morphological Sciences; Vol 4 No 3 (2021): JMS, 2021)
Stroke remains the second leading cause of death and the leading cause of disability worldwide, with its incidence and mortality differing between countries. Even though there has been a substantial decrease in the burden of stroke in high-income countries, around 70% of stroke cases occur in low or middle-income countries, with great negative effect on the system. Although risk factors are well known, it is still unclear to which extent each of them impacts the neurologic deficit and the level of consciousness of the patient.The aim of this study is to identify the influence of 6 common stroke risk factors - hypertension, atrial fibrillation, cardiomyopathy, diabetes mellitus, previous stroke or transient ischemic attack and dyslipidemia on the neurologic deficit quantified by National Institutes of Health Stroke Scale and the level of consciousness quantified by Glasgow Coma Scale. Material and methods: For this purpose, existing records of 157 patients from October 2019 to October 2020 were analysed.The study showed that atrial fibrillation (p=0.048), cardiomyopathy (p=0.024) and previous stroke or transient ischemic attack (p=0.03) significantly influence the mean National Institutes of Health Stroke Scale score, while atrial fibrillation (p=0.0067) and dyslipidemia (p=0.029) significantly influenced mean Glasgow Coma Scale scores. This emphasizes the need of proper management of risk factors, especially higlighting stroke prevention in atrial fibrillation. Keywords: stroke, risk factors, neurologic deficit, level of consciousness. https://doi.org/10.55302/JMS2143183a